Effects of Self-myofascial Release Using a Foam Roller on Range of Motion and Morphological Changes in Muscle: A Crossover Study. Issue 9 (September 2021) - Yoshimura, Akane; Inami, Takayuki; Schleip, Robert; Mineta, Shinshiro; Shudo, Kohei; Hirose, Norikazu
Abstract : Abstract: Yoshimura, A, Inami, T, Schleip, R, Mineta, S, Shudo, K, and Hirose, N. Effects of self-myofascial release using a foam roller on range of motion and morphological changes in muscle: a crossover study. J Strength Cond Res 35(9): 2444–2450, 2021—Self-myofascial release using a foam roller (FR) is effective in improving range of motion (ROM) in at least some conditions. However, its mechanism is still unclear. Therefore, this study investigated potential acute muscle morphological changes after the FR intervention and aimed to clarify the mechanism of increases in ROM by the FR intervention. We hypothesized that the FR intervention may increase ROM because of changes in fascicle length (FL) and aponeurosis displacement. This crossover study, involving 22 male university students (21.5 ± 1.3 years, 170.6 ± 4.0 cm, and 64.1 ± 8.9 kg; mean ± SD ), compared the FR intervention targeting the gastrocnemius muscle with the control trial. The outcome measures were maximum passive ankle ROM, morphology of the gastrocnemius muscle (FL and aponeurosis displacement) during passive ankle plantar flexor movement, degree of pain during the FR intervention, and sensation of the triceps surae muscle. Although ROM of both dorsiflexion and plantar flexion increased significantly after the FR intervention ( p < 0.01), no significant differences were found in FL and aponeurosis displacement before and after the FR intervention. The mean perception of pain during the FR intervention was rated as "slightly uncomfortable, " corresponding to a 2.3 ± 2.4-cm on a 9.5-cm visual analog scale. We found that the FR intervention did not influence the morphology of muscle. It is necessary to investigate other factors related to ROM as the next step of this study.